FACTORS OF CONSOLIDATION OF UKRAINIAN PEOPLE IN THE POLITICAL PROGRAMS OF DISSIDENTS (THE END OF THE 1950S TO THE BEGINNING OF THE 1960S) - Shevchenko, Tetiana (Київський національний університет імені Тараса Шевченка, 2018)
An activity of the Ukrainian Workers and Peasants Union (UWPU) headed by Levko Lukyanenko in West Ukraine  at the end of the 1950s to the beginning of the 1960s was a manifestation of the struggle for independence of Ukraine.  Contemporary historiography studies the UWPU’s activity in the context of looking for new forms and methods of the political  resistance to the Soviet system in West Ukraine without using the ideology of the Organization of Ukrainian Nationalists. The  result of the struggle depended on the ability to consolidate a whole society by the leaders of the national liberation movement. In  the article we shall study the ideas about unity of the Ukrainian society and potential factors of its consolidation in the program  documents of the UWPU. A task in hand of the UWPU was “to unmask before workers and peasants an irreconcilable opposite  of their interests and the interests of the bureaucratic officialdom as well to compel the direction to comply in the sphere of  increasing freedoms of people. Nevertheless an addition complication in the UWPU’s propaganda in West Ukraine was  Lykyanenko’s and Kandyba’s, the leading members’ belonging to the system of the Soviet justice which was a part of the party  and state structure and estranged deeply from people. The UWPU proclaimed a start of a new stage of struggle for the  independence of Ukraine by the most conscientious workers and peasants which are united all over Ukraine and do not  communicate with each other. The struggle of the UWPU for Ukraine’s secession from the USSR should be peaceful and  according to the Soviet constitution on the tactic and ideological grounds. The UWPU has thought that the idea of the  independent Ukraine is only one possible idea which could unite the whole Ukrainian people, exploited by the Russian Soviet  colonialist polotics workers and peasants deprived of their rights. The programme of the Union opposed the whole Ukrainian  people to the Ukrainian Communists, the representatives of the party and state officialdom, as obedient representatives of the  colonial administration. The members of the UWPU, high-principled Marxists, proclaimed their unstinting support the struggle of  the Ukrainian Uprising Army for the independence of Ukraine and blamed an armed repression by the Soviet state the Ukrainian  underground in West Ukraine. Taking into account the Ukrainian people changed during centuries of slavery and a social  oppression the UWPU’s programme does not only presume to challenge the presence of the protest potential of the Ukrainian  people but also affirms that in time the Ukrainian people’s aspiration to independence develops widely and its struggle for the  independence becomes fiercer. The UWPU suggests to campaign among workers and peasants for the uniting the whole  Ukrainian people for the struggle for Ukrainian state independency, as well to win representatives of other nationalities which live  in Ukraine, and fight for general democratization of the state structure in the USSR.  Key words: Levko Lukyanenko, Ukrainian Workers and Peasants Union, Ukrainians, national issue, social issue, Russian  colonialism

Стаття розглядає питання єдності українського народу та чинники його консолідації в програмних  документах Української робітничо-селянської спілки (УРСС) на чолі з Левком Лук‘яненком. Автор проаналізував  програмні засади та цілі УРСС, пов’язані з характеристикою соціального, національного і культурного становища  українців в СРСР, способами розв’язання національних, соціальних і культурних проблем українського народу, його  колоніального становища в СРСР, а також використання марксистсько-ленінської ідеології та риторики у  відстоюванні інтересів українського народу. Стаття представляє погляд на державотворчий потенціал українського  народу його інтелектуальної і політичної еліти, українських юристів. Дослідження висвітлює історичну  характеристику українського народу, дану в програмі УРСС, плановані способи реалізації політичної програми в  контексті єдності українського народу та його безсумнівного прагнення створити на даному історичному етапі  власну державу. Окрему увагу робота приділяє розгляду питання про єдність українського народу в контексті  висвітленого в програмі УРСС соціального розшарування – його поділу на українських комуністів-представників  колоніальної адміністрації, та трудовий народ.  Ключові слова: Левко Лук‘яненко, Українська робітничо-селянська спілка, українці, національне питання,  соціальне питання, російський колоніалізм
ЧИННИКИ КОНСОЛІДАЦІЇ УКРАЇНСТВА В ПОЛІТИЧНИХ ПРОГРАМАХ ДИСИДЕНТІВ (КІНЕЦЬ 1950-Х – ПОЧАТОК 1960-Х РОКІВ)